The Development of Learning Module on the Subject Matter of Colloidal System Based on Guided Inquiry at 11th Grade of SMA - Zulmariko; Mawardi; Budhi Oktavia (Fakultas Ilmu Pendidikan UNP)
This study aims to develop a learning module of chemistry based of guided inquiry in colloidal system and reveal the validity, practicality, and effectiveness of chemistry learning module subject of guided inquiry-based colloidal system. This learning module is tested on grade 11th’s students of SMAN 2 Painan, and has a reliability of 0.615. This research concludes that the chemistry learning module of the subject of colloid system based on guided inquiry is feasible to be used as a high school chemistry learning module